2007
DOI: 10.1007/s10350-006-0878-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iloprost on Impaired Anastomotic Healing Caused by 5-Fluorouracil plus Leucovorin

Abstract: The immediate postoperative, intraperitoneal administration of iloprost counteracts and reverses the negative effects of 5-fluorouracil plus leucovorin chemotherapy and protects colonic healing in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
5
0
4
Order By: Relevance
“…In the microscopic analysis, the muscular layer of the iloprost treated group appeared more natural as well as healthier than the colitis group. The beneficial effects of the same dose and application route of iloprost that we applied in the study had also been reported in previous studies investigating colon ischemia and anastomotic healing in Wistar albino rats (24,25).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the microscopic analysis, the muscular layer of the iloprost treated group appeared more natural as well as healthier than the colitis group. The beneficial effects of the same dose and application route of iloprost that we applied in the study had also been reported in previous studies investigating colon ischemia and anastomotic healing in Wistar albino rats (24,25).…”
Section: Discussionsupporting
confidence: 79%
“…This study presented an original idea and beneficial results were well documented in the study, however the difference of the method from the ischemia model of colon was not well defined (23,24). Ischemic colitis is difficult to evaluate experimentally, as ischemia is only one part of the complex pathogenesis of ischemic colitis (25,26). The parameter for which they evaluated utilizing microscopy could have been changed in part to the actual ischemia, rather than as a result of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…K.Vasiliadis also used the drug intraperitoneally at the same dosage to counteract the side effects of the chemotherapeutic agents and to improve the healing of the colonic anastomoses 12 .…”
Section: Histopathological Resultsmentioning
confidence: 99%
“…The dosage was calculated by reviewing literature about the amount of iloprost that was effective on the ischemic tissue and the amount was given as a single dose after the surgery iloprost was administrated in the early period after the laparatomy to the rats in groups 1 and 3 12,13 . …”
Section: Iloprost Therapymentioning
confidence: 99%
“…Animal models have been used extensively to study causality and underlying pathophysiological mechanisms, as well as the assessment of techniques and products that reinforce the anastomosis or improve healing. The study of anastomotic failure in animals involves moderate to severe animal discomfort, dedicated human effort and considerable cost.…”
Section: Introductionmentioning
confidence: 99%